1999
DOI: 10.1007/bf02235191
|View full text |Cite
|
Sign up to set email alerts
|

Squamous-cell carcinoma of the colon responsive to combination chemotherapy

Abstract: Primary squamous-cell carcinoma of the colon is a rare malignancy of unknown cause and pathogenesis. Metastatic tumors to the colon should be ruled out in all cases before therapy. Early detection and surgery remain the main therapeutic options, but as presented in our case, response to chemotherapy in advanced disease is encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 38 publications
1
57
0
Order By: Relevance
“…In mixed adenosquamous variety, Cerezo and others suggested that all such lesions be carefully evaluated by means of immunoperoxidase stains and/or electron microscopy in order to identify squamous features [20,21]. Symptoms, investigations, and assessment of patients with the divergent histologic subtypes of squamous cancer of the colon and rectum, including basaloid tumors, are similar to those of colon adenocarcinoma, as is evident in our case [5,22]. However, the prognosis of patients with colorectal SCC is difficult to establish due to the rarity of these tumors.…”
Section: Discussionsupporting
confidence: 57%
“…In mixed adenosquamous variety, Cerezo and others suggested that all such lesions be carefully evaluated by means of immunoperoxidase stains and/or electron microscopy in order to identify squamous features [20,21]. Symptoms, investigations, and assessment of patients with the divergent histologic subtypes of squamous cancer of the colon and rectum, including basaloid tumors, are similar to those of colon adenocarcinoma, as is evident in our case [5,22]. However, the prognosis of patients with colorectal SCC is difficult to establish due to the rarity of these tumors.…”
Section: Discussionsupporting
confidence: 57%
“…18 A populationbased study of anal epidermoid carcinomas did not reveal a sex-specific difference. 19 However, a study using data from the Utah cancer registry found a greater proportion of squamous cell cancers (listed as a subtype of epidermoid cancers in this study) in females.…”
Section: Discussionmentioning
confidence: 95%
“…The pathogenesis of these tumors is poorly understood but may involve squamous de-differentiation of a pre-existing adenocarcinoma or squamous metaplasia progressing to dysplasia and carcinoma as a result of a chronic inflammatory stimulus (1)(2)(3)(4)(5). In the present case, the presence of squamous metaplasia in the adjacent mucosa suggests the latter.…”
Section: Discussionmentioning
confidence: 70%